The use of songs as a tool to work on listening and culture in EFL classes - Reina Arévalo, Edgar Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This article presents an action research study applied in a second level EFL course at a university in Tunja. The study examines the listening performance of students throughout the development of six workshops based on the songs: Englishman in New York, Imagine, Mercedes Benz, Cats in the cradle, Zombie, and Where is the love? Findings of this study indicate that this type of material can foster listening skills and engage students in discussion about cultural and social issues. Likewise, results show that practicing listening with songs can become a good way to train students in the development of higher levels of comprehension.